A platform for programming autonomous robots - Mohamed Shaheer Thurabsha Haja (2016)
This report is done as a final year project (FYP), as partial fulfilment of the requirements of the Bachelor of Engineering (EEE) program at Nanyang Technological University (NTU). The main objective of this project is to aid ordinary users into programming, by offering them a platform to input robotic logic into a wheeled ground robot.